Analisis Pengaturan Ahli Waris Pengganti dalam Hukum Waris di Indonesia - Sukran Jamil; Ahmad Bardi (CV. Ulil Albab Corp, 2024)
A replacement heir is a person who is given the right to act to replace the position of an heir who has died before the heir, provided that the person concerned is not prevented by law from acting as an heir. According to Article 185 KHI, heirs who die before the testator can be replaced by their children, provided that the share of the successor heir cannot exceed the share of the heir who is equal to the one being replaced. The problem examined in this research is what is the position of the successor heir and the protection of his rights according to the Civil Code and the Compilation of Islamic Law? The research method used is a normative legal research method with a conceptual approach and statutory regulations. The primary legal materials used in this research are legal materials that are authoritative, meaning they have authority, such as statutory regulations, official records or minutes in making legislation and judges' decisions. The research results show that the statutory regulations governing successor heirs are more than one law, namely in the Civil Code and the Compilation of Islamic Law. The rights of substitute heirs receive protection from the State by stipulating that the rights of substitute heirs can replace the position of heirs who have died before him.